“Impact of Educational Background on Academic Scores of Management Students: Case Study” - Morani, Renuka; Jain, Arjita (Gyan Management Journal, 2022)
Identifying the factors that influence academic performance of students is  an essential part of educational research. Previous studies have documented  the importance of personality traits, class attendance, parenting etc. This  paper is aimed at evaluating the Influence of Stream of Graduation on  Academic Score of Management Students. For this purpose, data was  collected from a sample of 60 MBA students enrolled with a management  institute of Navi Mumbai. Descriptive Statistics, One-way ANOVA and  Tukey Honestly Significant Difference (HSD) Test was used for analysis.  The first-year’s Academic Scores were taken as a measurement of Academic  Performance of the MBA students. The results of the study revealed that  there is no significant difference in Academic Scores of the MBA students  from different educational background. The Levene’s Test revealed that the  variance of all groups i.e B. Com, BMS and B.Sc. were equal. Tukey HSD  test further confirmed that the academic scores of students having different  background doesn’t significantly differ.
Keywords: Academic Performance; Academic Scores; Graduation Stream; Management Studies; MBA